Compressible fluid flow - Oosthuizen, P.H (McGraw-Hill, 1997)
This text provides clear explanations of the physical phenomena encountered in compressible fluid flow by providing more practical applications, more worked examples, and more detail about the underlying assumptions than other texts. Its broad topic coverage includes a thorough review of the fundamentals, a wide array of applications, and unique coverage of hypersonic flow. This is the ideal text for compressible fluid flow or gas dynamics courses found in mechanical or aerospace engineering programs.